RELIGIUSITAS DALAM SYAIR AYYA MAN YADDAIL FAHM KARYA AL-HARIRI: RELIGIOSITY IN THE POEM AYYA MAN YADDA’IL FAHM BY AL-HARIRI - Harlan Darmawan; Fadlil Yani Ainusyamsi; Ade Ahmad Suprianto (Universitas Batanghari, 2026)
This research is motivated by the pervasive dominance of contemporary materialistic culture which creates the phenomenon of simulacra, where transcendental values are often obscured by shallow imagery that has lost its referential reference to the divine. In response to this spiritual crisis, this study aims to uncover the systematic construction of religiosity in the classic poem Ayya Man Yadda’il Fahm by Al-Hariri through the triadic semiotic approach of Charles Sanders Peirce. The research method employed is a descriptive qualitative approach utilizing the interactive model analysis procedure of Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing/verification. The results show that the sign mechanism in the poem is massively dominated by Index signs which have physical causality relationships, particularly within the indicators of Piety (Takwa) and Repentance (Tobat). Al-Hariri strategically utilizes biological